Determinants of COVID-19 Vaccine Acceptance and Hesitancy: A Systematic Review - Juliana Soares Tenório De Araújo; Felipe Mendes Delpino; Rubia Laine de Paula Andrade-Gonçalves; Francisca Bruna Arruda Aragão; Letícia Perticarrara Ferezin; Denise Alves Santos; Neemais Costa Duarte Neto; Murilo César do Nascimento; Simão Pedro Tavares Moreira; Gabriela Ferreira Ribeiro; Rayssa Francielly dos Santos Alves; Ricardo Alexandre Arcêncio (Vaccines)
Background/Objectives: COVID-19 is an infectious disease whose prevention is significantly aided by vaccination, which reduces both case severity and mortality. Despite the safety and efficacy of vaccines, acceptance is not universal, and understanding of the factors influencing vaccination decisions and hesitancy remains limited. This review aims to identify and analyze studies addressing two key questions: what influences the decision to vaccinate and what factors are associated with vaccine hesitancy. Methods: This systematic review was conducted following the PRISMA guidelines. Data collection utilized descriptors related to vaccine adherence and hesitancy, based on the PEO strategy of the Joanna Briggs Institute (JBI). Searches were conducted in Embase, Scopus, PubMed, Lilacs, and Web of Science, focusing on publications from 2021, the year the first COVID-19 vaccine was approved. After excluding duplicates and selecting articles based on eligibility criteria, the analysis involved data extraction and methodological quality assessment using JBI tools. Results: A total of 5268 publications were identified, with 30 included in this study. Factors associated with vaccine hesitancy included low education levels, social media influence, confidence in vaccine safety, and fear of side effects. In contrast, factors linked to vaccine acceptance included higher education, higher income, older age, and existing comorbidities. Conclusions: The findings highlight the urgent need for targeted health communication and education strategies, particularly for vulnerable groups. Public health policies should incorporate these factors to enhance vaccination adherence and build public confidence in vaccine safety, which is essential for mitigating future health emergencies.